Clinical correlates of the "rods and rings" antinuclear antibody pattern. (17th February 2016) - Climent, Joan; Morandeira, Francisco; Castellote, José; Xiol, Javier; Niubó, Jordi; Calatayud, Laura; Mestre, Mariona; Bas, Jordi
Abstract: The "rods and rings" (RR) antinuclear antibody (ANA) pattern is believed to be restricted to hepatitis C virus (HCV) infection and related to the treatment. This is a 4-year retrospective study of all patients with RR pattern from the 20 000 serum samples received at the Hospital Universitari de Bellvitge for ANA testing. Two control groups with HCV patients without RR pattern: ANA-positive ( n = 74) and ANA negative ( n = 75) were included. Eighty-seven patients had samples with the RR pattern. Seventy-three were infected with HCV (prevalence of 15% in the HCV population). The RR pattern could not be related to ribavirin treatment, clinical status, biochemistry data, hepatic fibrosis, IL28B genotype, HCV genotype or the presence of autoantibodies related with autoimmune hepatitis. As 14 cases presented other diseases, mainly of autoimmune origin, the presence of RR antibodies may also be explained by alterations in immune regulation caused by autoimmunity or HCV in a particular genetic background.